Bibliography of Books for Children - Roedder, Kathleen R., Comp.; Sidorsky, Phyllis G., Comp.; Association for Childhood Education International, Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1980)
Intended for use by librarians, teachers, parents, and community workers as a guide to good children's literature, this annotated bibliography contains more than 1,000 entries. Each entry provides author and title, publisher, date of publication, price, and International Standard Book Number (ISBN). Age level is also indicated. The entries are arranged under the following headings: (1) picture books; (2) easy reading; (3) fiction; (4) story collections; and (5) nonfiction, including philosophy/psychology, religion, social studies, folklore and legends, language, physical science, earth science/biology/botany, animal kingdom, technology, arts/recreation, poetry/plays, geography, biography, and history. The guide also contains a list of selected reference collections for an elementary school library, a directory of publishers, and title and author indexes. (FL)
Availability: Association for Childhood Education International, 3815 Wisconsin Ave., NW, Washington DC 20016 ($5.95 plus 10% postage/handling).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Annotated Bibliographies; Books; Childrens Literature; Elementary Secondary Education; Fiction; Nonfiction; Picture Books; Reading Instruction; Reading Interests; Reading Material Selection; Reference Materials, Bibliographies